Glutamate Transporters in Hippocampal LTD/LTP: Not Just Prevention of Excitotoxicity - Gonçalves-Ribeiro, Joana; Pina, Carolina Campos; Sebastião, Ana Maria; Vaz, Sandra Henriques (Frontiers in Cellular Neuroscience, 2019)
Glutamate uptake is a process mediated by sodium-dependent glutamate transporters, preventing glutamate spillover from the synapse. Typically, astrocytes express higher amounts of glutamate transporters, thus being responsible for most of the glutamate uptake; nevertheless, neurons can also express these transporters, albeit in smaller concentrations. When not regulated, glutamate uptake can lead to neuronal death. Indeed, the majority of the studies regarding glutamate transporters have focused on excitotoxicity and the subsequent neuronal loss. However, later studies have found that glutamate uptake is not a static process, evincing a possible correlation between this phenomenon and the efficiency of synaptic transmission and plasticity. In this review, we will focus on the role of the increase in glutamate uptake that occurs during long-term potentiation (LTP) in the hippocampus, as well as on the impairment of long-term depression (LTD) under the same conditions. The mechanism underpinning the modulatory effect of glutamate transporters over synaptic plasticity still remains unascertained; yet, it appears to have a more prominent effect over the N-methyl-D-aspartate receptor (NMDAR), despite changes in other glutamate receptors may also occur.